Acceptability of COVID-19 vaccination among health care workers: a cross-sectional survey in Morocco - Mohamed Khalis; Asmaa Hatim; Latifa Elmouden; Mory Diakite; Abdelghafour Marfak; Soukaina Ait El Haj; Rachid Farah; Mohamed Jidar; Kaba Kanko Conde; Kenza Hassouni; Hafida Charaka; Mark Lacy; et al. (Taylor & Francis Group, 2021)
Introduction This study aimed to evaluate the acceptability of COVID-19 vaccination among health care workers prior to the start of the COVID-19 vaccination campaign in Morocco. Methods This cross-sectional study was conducted in the Cheikh Khalifa University Hospital of Casablanca-Morocco. Utilizing a web-based platform surveys were distributed over a 3-week period via professional mailing list and social media. Odds ratios and 95% confidence intervals were estimated by using logistic regression models. Results A total of 303 health care workers participated in this study. The results showed a relatively high rate of vaccination acceptability (62.0%) among health care workers included in this study. Participants were more likely to accept the COVID-19 vaccine if they were physician, nurse, or technician (OR 1.79; 95% CI: 1.09-2.95), had high score of confidence in the information circulating about COVID-19 (OR 1.91; 95% CI: 1.36-2.69), or had high score of perceived severity of COVID-19 (OR 1.55; 95% CI: 1.11-2.15). Reasons of hesitation/or refusal of COVID-19 vaccine were fear of the likely side effects of the vaccine for 74.8% of participants, and concern about the effectiveness of the vaccine for 47.8%. Conclusion This study showed a relatively high rate of the COVID-19 vaccination acceptance among health care workers in Morocco. Willingness to be vaccinated was significantly associated with job category, confidence in the information circulating about COVID-19, and perceived severity of COVID-19. These results could be useful in the development of educational interventions to increase the acceptance of COVID-19 vaccine among health care workers in Morocco and similar settings.